Đáp án:
Giải thích các bước giải:
`P=\frac{\sqrt{x}-3}{\sqrt{x}+3}+\frac{2\sqrt{x}}{1-\sqrt{x}}+\frac{26\sqrt{x}-19+x\sqrt{x}}{x+2\sqrt{x}-3}`
ĐK: `x \ge 0, x \ne 1`
`P=\frac{(\sqrt{x}-3)(\sqrt{x}-1)}{(\sqrt{x}-1)(\sqrt{x}+3)}-\frac{2\sqrt{x}(\sqrt{x}+3)}{(\sqrt{x}-1)(\sqrt{x}-3)}+\frac{26\sqrt{x}-19+x\sqrt{x}}{(\sqrt{x}-1)(\sqrt{x}-3)}`
`P=\frac{(\sqrt{x}-3)(\sqrt{x}-1)-2\sqrt{x}(\sqrt{x}+3)+26\sqrt{x}-19+x\sqrt{x}}{(\sqrt{x}-1)(\sqrt{x}-3)}`
`P=\frac{x-4\sqrt{x}+3-2x-6\sqrt{x}+26\sqrt{x}-19+x\sqrt{x}}{(\sqrt{x}-1)(\sqrt{x}-3)}`
`P=\frac{-x-16+16\sqrt{x}+x\sqrt{x}}{(\sqrt{x}-1)(\sqrt{x}-3)}`
`P=\frac{(\sqrt{x}-1)(x+16)}{(\sqrt{x}-1)(\sqrt{x}-3)}`
`P=\frac{x+16}{\sqrt{x}-3}`